Analysis of Online Learning on Students’ Understanding and Learning Motivation with Lecturer Competence as Moderating Variable (Studies During the Covid-19 Pandemic) - Tegowati Tegowati; Wininatin Khamimah; Dewi Mutmainnah; Nenny Syahrenny; In’am Widiarma (Universitas Pendidikan Mandalika (UNDIKMA), 2022)
The purpose of this study was to analyze the impact of online learning on students' understanding and learning motivation with lecturer competence as a moderating variable. This research method used a survey method. The population in this study were all STIESIA Surabaya students and the sample in this study were STIESIA Surabaya students who were taking online lessons during the Covid-19 pandemic. The sample is 100 students and the sample was taken using non-probability sampling. Data collection techniques were carried out through online questionnaires given to STIESIA Surabaya students. The data analysis technique used SEM with a moderating relationship using AMOS 21 software. The results of this study indicated that (1) online learning has a positive and significant effect on student understanding; (2) online learning does not affect students' learning motivation; (3) Online learning has a positive and significant effect on students' understanding with lecturer competence as a moderating variable; 4) Online learning has no positive and significant effect on student learning motivation with lecturer competence as a moderating variable (lecturer competency is not a moderating variable or is not a moderating variable between online learning and student learning motivation). Based on the results of the research stated, it is hoped that it can help the learning process give implications for increasing student understanding during online lectures by maximizing the competence of lecturers.